A Study on the Improvement Plan of Facility in National Park Using Importance-Performance Analysis - BAE, Joonho; NAM, Seungmin (Journal of Environmental Management and Tourism; Vol 11 No 1 (2020): JEMT Volume XI Issue 1(41) Spring 2020, 2020)
The purpose of this study is to provide comprehensive analysis and improvement plan for national park facility plan. Specific purpose is following. First, this study analysed the characteristics of the use of national park facilities through questionnaire surveys the Importance-Performance Analysis (IPA). Second, this study plans to find ways to improve the facilities of national parks such as new types of park facilities, laws and systems. This study was conducted at six national parks located in the following major Korean provinces: Kyeongnam, Jeonbuk, Kyeongbuk, Seoul, Jeonnam and Gangwon which are Geoje, Byeonsan, Kyeongju, Bukhansan, Jirisan, Seoraksan national parks